Reviews and Interviews - Warso, Anna; Pietrzak, Wit; Ojrzyńska, Katarzyna; Jędrzejewski, Jan; Uchman, Jadwiga (Text Matters: A Journal of Literature, Theory and Culture, 2018)
Anna Warso: Songs of America: A Review of John Berryman’s Public Vision by Philip Coleman (Dublin: UCD P, 2014) Wit Pietrzak: Yeats, Incorrigibly Plural. A Review of Barry Shiels’s W. B. Yeats and World Literature: The Subject of Poetry (Farnham: Ashgate, 2015) Katarzyna Ojrzyńska: “Disability demands a story”: A Review of Stewart Parker’s Hopdance (ed. Marilynn Richtarik, Dublin: Lilliput, 2017) Building Bridges: From Łódź to Ulster and Back. Jadwiga Uchman Interviews Jan Jędrzejewski